Nuclear localization and upregulation of BAI1 in alveolar macrophages during LPS-Induced acute lung injury - A-Guo Li; Xiao-Ye Huang; Ken-Qi Zhang; Ping Xu; Hong-Yan Wang; Ye-Ping Yao; Yong-Sheng Tu (Scientific Reports)
Abstract Brain-specific angiogenesis inhibitor-1 (BAI1) is an endocytic scavenger receptor that mediates macrophage clearance of apoptotic or phosphatidylserine-expressing cells. Previous studies have shown that BAI1 was localized in the cellular cytoplasm and membrane. However, currently there is no available information regarding the distribution of BAI1 expression in alveolar macrophages (AMs) or its specific role in acute lung injury (ALI). The aim of this study was to preliminarily investigate BAI1 expression in AMs and changes in BAI1 expression levels in an ALI model. A mouse model of ALI was established through intratracheal instillation of a 2 mg/kg LPS. The expression of BAI1 in lung tissues was quantified using immunohistochemistry staining, while the expression of BAI1 in AMs in bronchoalveolar lavage fluid (BALF) was examined through immunofluorescence. Additionally, the MH-S cells were treated with LPS to investigate the distribution and changes in BAI1 expression levels, which were detected using immunofluorescence and Western Blot. Results showed that BAI1 protein was found to be localized in the cellular nuclei in AMs. Moreover, the BAI1 expression level was observed to escalate with the rising concentration of LPS in MH-S cells and in AMs of lungs from ALI mice. Finally, the upregulation of BAI1 expression in MH-S cells induced by LPS was associated with a decrease in the efferocytosis of MH-S cells. The discovery of BAI1 expression in the nuclei of AMs in ALI mice is a novel finding. It is plausible that BAI1 protein may participate in efferocytosis of AMs during ALI through novel signaling pathways.